The Digital Marketing Model Uses Social Media to Get Out Of The Economic Crisis Caused By Covid 19 - Putra, Saiful Aminudin Al Kusuma; Sucipto, Beni; Rachmadana, Satria Lintang (Journal of Economics Education and Entrepreneurship, 2022)
The phenomenon of covid-19 has not been completed because the virus continues to mutate from the alpha, delta, gamma to Omicron variants, this variant is more virulent and quickly spreads than the previous variant. The impact is still being felt today. This study aims to investigate how SMEs can deal with crises and the strategies they have used to maintain their business, to prepare SMEs for future crises. The population in this study are SMEs who are members of the Institute for Modern Creative Industries (LIKM). The sampling technique used purposive sampling technique with 6 sources. This research is a type of qualitative research with a case study approach. The type of case study used is a collective or multiple case study. This study uses primary data. Data collection techniques used in this study were interviews and observation. The data analysis technique used is the spiral model technique. The results of this study, so that SMEs can survive the strategy used is to increase advertising and promotion through social media. Marketing using social media clearly has a very high effectiveness and contributes to sales volume. The marketing model found shows that the higher the understanding of business actors on the potential of digital marketing using social media, the more precise they will be in choosing a marketing model using social media